Digital TV comes down to earth. - Fox, B. (IEEE spectrum)
The introduction of digital television, albeit with only modest pretensions to glitz, is bound to invigorate competition among manufacturers and broadcasters. The BBC and commercial TV companies in Britain will launch what looks to be the world's first terrestrial digital TV (DTTV) service intended for nationwide viewing. The British services will be the first to use ground transmitters to send digital pictures and sound to an ordinary Yagi roof antenna of the type used for analog TV in Europe or even to indoor rabbit ears. Plenty of digital receivers should be in the shops, and pay TV services, both satellite and terrestrial, will be wooing hesitant viewers with special incentives. Most other countries in Europe are also getting ready to launch DTTV services. The author discusses the phase out of analog services, digital video broadcasting standards, data rates, encryption standard, and competing digital services